2017
DOI: 10.1089/lrb.2016.0035
|View full text |Cite
|
Sign up to set email alerts
|

SF-36 Shows Increased Quality of Life Following Complete Reduction of Postmastectomy Lymphedema with Liposuction

Abstract: AbstractsBackground: Arm lymphedema after breast cancer surgery affects women both from physical and psychological points of view. Lymphedema leads to adipose tissue deposition. Liposuction and controlled compression therapy (CCT) reduces the lymphedema completely.Methods and Results: Sixty female patients with arm lymphedema were followed for a 1-year period after surgery. The 36-item short-form health survey (SF-36) was used to assess health-related quality of life (HRQoL). Patients completed the SF-36 quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 45 publications
2
60
0
1
Order By: Relevance
“…Nearly half of the study sample is age more than sixty-five. This finding is similar to (Mak et al, 2009) and (Mattias et al, 2017) who documented that occurrence of lymphedema significantly increases with age, as demonstrated in the present study. Finally, a minority of the study sample started treatment with radiotherapy, which is considered one of the risk factors.…”
Section: Table (7)supporting
confidence: 93%
“…Nearly half of the study sample is age more than sixty-five. This finding is similar to (Mak et al, 2009) and (Mattias et al, 2017) who documented that occurrence of lymphedema significantly increases with age, as demonstrated in the present study. Finally, a minority of the study sample started treatment with radiotherapy, which is considered one of the risk factors.…”
Section: Table (7)supporting
confidence: 93%
“…Using the 36-item short-form health survey (SF-36) to assess health-related quality of life in female patients who underwent upper extremity liposuction, Hoffner et al found that scores 12 months following the procedure were significantly improved for physical functioning, bodily pain, vitality, social functioning, and mental health compared with preoperatively, 42 supporting the findings of other studies. 43,44 In another study, using the Hospital Anxiety and Depression Score (HADS) questionnaires and a visual analogue score for overall well-being, significant reductions in anxiety and depression scores and an improvement in overall well-being were demonstrated following liposuction for lymphedema of the upper extremity.…”
Section: Improvement In Quality Of Lifementioning
confidence: 70%
“…Liposuction, which is effective in reducing limb volume, does not address the underlying disease process and is limited to patients in whom there is a significant adipose component. It does not obviate the need for ongoing CGT, and concern remains over liposuction worsening the fibrotic component of lymphoedema 7,12,13 . Although LNT may offer the possibility of anatomical lymphatic reconstruction, evaluating its true efficacy is difficult and donor-site morbidity remains a concern 22,38,39 ; however, a comprehensive discussion of its value is beyond the remit of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of BCRL is reported as approximately 20 per cent at 1 year and as high as 40 per cent at 10 years after breast cancer treatment. The impact, both psychological and physiological, on patients is unquestionable, and the complications of BCRL (cellulitis, ulceration) may require prolonged periods of specialist management. The tenets of lymphoedema management include patient education, skin care and control of coexisting medical conditions that may worsen swelling.…”
Section: Introductionmentioning
confidence: 99%